Influence of musculoskeletal system dysfunction degree on psychophysiological indicators of Paralympic athletes - Kozina, Z.; Lytovchenko, M.; Safronov, D.; Boichuk, Y.; Chaika, O.; Shepelenko, T.; Polianskyi, A.; Protsevskiy, V.; Peretyaha, L.; Konnova, M. (Sports, 2019)
The purpose of the work was to identify the influence of functional class and degree of damage to extremities on psychophysiological indicators of Paralympians. The study involved 33 elite athletes with musculoskeletal system disorders of the 6 (n = 15) and 10 (n = 18) functional classes in table tennis, aged 21-25 years old. Parameters characteristic for determining the psychophysiological state and typological characteristics of the nervous system were analyzed with the help of computer programs for psychophysiological testing. We determined the latent time of simple and complex reactions in different testing modes. Dispersion analysis was also used. We applied single-factor multidimensional dispersion analysis: one-way analysis of variance and General Linear Model, Multivariate. The indicators of psychophysiological testing were applied as dependent variables. The values of the functional class of athletes were used as the independent variable. To study the influence of damage degree of the upper or lower extremities on psychophysiological indicators, the extremities damage degree was applied as an independent variable. The time in the Paralympic 6 functional class to reach the minimum signal exposure in feedback mode was significantly longer compared with the 10 Paralympic functional class (p < 0.05). Comparing psychophysiological indicators when Paralympians are divided into groups more differentiated than functional classes (that is, according to the nature of the disease or the degree of limb lesions), significant differences were found in all psychophysiological indicators between the athletes of different groups. The greatest impact on psychophysiological indicators was a lesion of the lower extremities. The training of Paralympians in table tennis should consider the reaction rate indicators. In addition, when improving the functional classification of Paralympians in table tennis, a more differentiated approach should be taken when considering their capabilities, including psychophysiological indicators. During training and functional classification of Paralympic athletes in table tennis, it is important to consider their functional class as well as the degree of damage to upper and lower extremities and the level of psychophysiological functioning